2021
DOI: 10.1002/glia.24100
|View full text |Cite
|
Sign up to set email alerts
|

Blocking Kallikrein 6 promotes developmental myelination

Abstract: Kallikrein related peptidase 6 (Klk6) is a secreted serine protease highly expressed in oligodendrocytes and implicated in demyelinating conditions. To gain insights into the significance of Klk6 to oligodendrocyte biology, we investigated the impact of global Klk6 gene knockout on CNS developmental myelination using the spinal cord of male and female mice as a model. Results demonstrate that constitutive loss of Klk6 expression accelerates oligodendrocyte differentiation developmentally, including increases i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 73 publications
0
7
0
Order By: Relevance
“…Myelin sheath played an important role in learning and memory 6 . MBP, which mainly arose from the gene in the oligodendrocyte, was essential to the formation of the multilamellar myelin sheath of the mammalian central nervous system (CNS), 18 and CC‐1 was an important marker protein for oligodendrocyte labeling 19 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Myelin sheath played an important role in learning and memory 6 . MBP, which mainly arose from the gene in the oligodendrocyte, was essential to the formation of the multilamellar myelin sheath of the mammalian central nervous system (CNS), 18 and CC‐1 was an important marker protein for oligodendrocyte labeling 19 …”
Section: Resultsmentioning
confidence: 99%
“…6 MBP, which mainly arose from the gene in the oligodendrocyte, was essential to the formation of the multilamellar myelin sheath of the mammalian central nervous system (CNS), 18 and CC-1 was an important marker protein for oligodendrocyte labeling. 19 In order to investigate the relationship between cognitive deficiency and myelin sheath formation, as well as the number of oligodendrocytes, we detected the expression of MBP and the number of CC-1 + cells. We found that Sev dramatically downregulated the MBP expression in cortex (68.60% ± 4% vs. 49.9 ± 6%, p = 0.0298, In order to further study the effect of Sev on myelin formation, TME was used to detect the myelin morphology of cortical and hippocampal tissues, and the results showed that the g ratio of cortical and hippocampal myelin increased, which meant that Sev caused the reduction of myelin thickness, as shown in Figure 3.…”
Section: Sev Caused Cognitive Deficiency and A Decrease In The Expres...mentioning
confidence: 99%
“…It is also possible paracrine factors produced by more mature oligodendrocytes in the ipsilateral striatum influence progenitor cells. The reactive cell cluster over expresses Klk6 , which has been shown to limit OPC differentiation into myelinating cells (Yoon et al, 2022). On the other hand, reactive cells and ipsilateral MFOL/MOL cells have significantly upregulated expression of Apoe , and ApoE is known to promote oligodendrocyte differentiation (Gan et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…It is also possible paracrine factors produced by more mature oligodendrocytes in the ipsilateral striatum influence progenitor cells. The reactive cell cluster over expresses Klk6 , which has been shown to limit OPC differentiation into myelinating cells[81]. On the other hand, reactive cells and ipsilateral MFOL/MOL cells have significantly upregulated expression of Apoe , and ApoE is known to promote oligodendrocyte differentiation[82].…”
Section: Discussionmentioning
confidence: 99%